2010
DOI: 10.1371/journal.pone.0010329
|View full text |Cite
|
Sign up to set email alerts
|

Abundant Lipid and Protein Components of Drusen

Abstract: BackgroundDrusen are extracellular lesions characteristic of aging and age-related maculopathy, a major retinal disease of the elderly. We determined the relative proportions of lipids and proteins in drusen capped with retinal pigment epithelium (RPE) and in RPE isolated from non-macular regions of 36 human retinas with grossly normal maculas obtained <6 hr after death.Methodology/Principal FindingsDruse pellets were examined by light and electron microscopy. Component proteins were extracted using novel meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
276
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(285 citation statements)
references
References 87 publications
7
276
0
2
Order By: Relevance
“…The ionic signatures for other phospholipids and/or triglycerides were not detected at this spatial resolution. However, the spherules in sub-RPE deposits clearly contain calcium phosphate (these experiments did not distinguish the different calcium phosphates), and they are also associated with cholesterol and/or cholesteryl esters in accord with previous observations on the composition of extracellular lipid droplets in Bruch's membrane and sub-RPE deposits (11,30).…”
Section: Significancesupporting
confidence: 87%
“…The ionic signatures for other phospholipids and/or triglycerides were not detected at this spatial resolution. However, the spherules in sub-RPE deposits clearly contain calcium phosphate (these experiments did not distinguish the different calcium phosphates), and they are also associated with cholesterol and/or cholesteryl esters in accord with previous observations on the composition of extracellular lipid droplets in Bruch's membrane and sub-RPE deposits (11,30).…”
Section: Significancesupporting
confidence: 87%
“…Histologically, patients with early stages of AMD are characterized by the presence of drusen, extracellular debris that accumulates between the retinal pigment epithelium (RPE) and Bruch's membrane. Studies of the composition of drusen revealed extracellular matrix proteins as well as inflammatory molecules as the major components of drusen (Crabb et al., 2002; Wang et al., 2010). Many of the extracellular matrix proteins with increased expression in AMD high‐risk RPE cells from our data were also found in proteomic analyses of drusen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if the CFH Y402H risk mutation lowers its affinity for CRP, then the lack of inhibition might be expected to trigger overactive inflammation in the extracellular space. The CFH risk allele is associated with increased soft drusen in the eye, and immunohistochemical and proteomic studies of drusen composition revealed several complement proteins in addition to CFH (Crabb et al., 2002; Magnusson et al., 2005; Wang et al., 2010). Several clinical trials have tried using anti‐inflammatory agents to target the complement system and systemic inflammation, but these had limited success (Ambati, Atkinson & Gelfand, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of lipid composition in BrM has suggested that the lipoprotein particles are different from those found in plasma. They contain free and esterified cholesterol (37), phosphatidylcholine, and apolipoprotein B100 (38), and differ in composition such as their enrichment for esterified cholesterol and the percent phospholipid being comprised of phosphatidylcholine (39). It is suggested that the lipoproteins in BrM may be derived in part from the photoreceptor outer segments, but are processed significantly by the RPE (40).…”
mentioning
confidence: 99%